2013
DOI: 10.3109/00498254.2013.861950
|View full text |Cite
|
Sign up to set email alerts
|

Application of a liquid chromatography–tandem mass spectrometry method to the pharmacokinetics, bioavailability and tissue distribution of neohesperidin dihydrochalcone in rats

Abstract: 1. This study was aimed at developing a high sensitive and selective liquid chromatography-tandem mass spectrometry method to quantify neohesperidin dihydrochalcone (NHDC) in rat plasma and tissues for pharmacokinetic, bioavailability and tissue distribution studies. 2. Biological samples were processed with one-step protein precipitation. Rutin was chosen as the internal standard (IS). Chromatographical separation was achieved on an SB-C18 (2.1 mm× 150 mm, 5 μm) column with acetonitrile--0.1% formic acid in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The reactions occurred at the hydroxyls of the C-2', C-4', and C-6' position. Wang et al (2014) estimated a plasma half-life of 1.0 AE 0.2 h and a volume of distribution of 1.2 AE 0.49 L/kg.…”
Section: Summary and Conclusion On Admementioning
confidence: 99%
See 4 more Smart Citations
“…The reactions occurred at the hydroxyls of the C-2', C-4', and C-6' position. Wang et al (2014) estimated a plasma half-life of 1.0 AE 0.2 h and a volume of distribution of 1.2 AE 0.49 L/kg.…”
Section: Summary and Conclusion On Admementioning
confidence: 99%
“…In vivo ADME data are only available from two studies in rats, with one assessing metabolites as well as the parent compound. Wang et al (2014) estimated the systemic availability of neohesperidine dihydrochalcone in rats as being 21.8%. Zhang et al (2021) identified 19 components in the urine, among them the parent compound besides several metabolites, mostly glucuronides, sulfates and other conjugates which were also formed after hydrolysis of neohesperidine dihydrochalcone to hesperetin dihydrochalcone.…”
Section: Summary and Conclusion On Admementioning
confidence: 99%
See 3 more Smart Citations